2020
DOI: 10.1177/1363461520920329
|View full text |Cite
|
Sign up to set email alerts
|

Migration-related emotional distress among Vietnamese psychiatric patients in Germany: An interdisciplinary, mixed methods study

Abstract: Culture and socialization influence how individuals perceive and express emotional distress. Research therefore, must consider the context to capture individual experiences. However, the majority of studies on factors associated with emotional distress among migrants use quantitative approaches, limiting an in-depth understanding. This study investigates emic themes of emotional distress among Vietnamese migrants by integrating anthropological and psychiatric approaches. The mixed methods study first quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…This study aims to help address the knowledge gap about mental health in non-WEIRD countries, with a specific focus on Myanmar. As this is the first study to investigate loneliness in Myanmar’s older population, a mixed-methods approach was used, as it has the powerful advantage of being able to complement quantitative measures with individuals’ reports about their lived experiences (e.g., Haroz et al, 2017 ; Nguyen et al, 2021 ). In research on global mental health, it is well-known that quantitative measures of theoretical constructs may not correspond to individuals’ culturally specific understandings of mental health (e.g., depression, loneliness).…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to help address the knowledge gap about mental health in non-WEIRD countries, with a specific focus on Myanmar. As this is the first study to investigate loneliness in Myanmar’s older population, a mixed-methods approach was used, as it has the powerful advantage of being able to complement quantitative measures with individuals’ reports about their lived experiences (e.g., Haroz et al, 2017 ; Nguyen et al, 2021 ). In research on global mental health, it is well-known that quantitative measures of theoretical constructs may not correspond to individuals’ culturally specific understandings of mental health (e.g., depression, loneliness).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural immersion provides an individual with a sense of belonging. Studies have demonstrated that belonging, defined as an emotionally charged position in social structure, experienced through identification, embeddedness, connectedness, and attachments (Pfaff-Czarnecka, 2013), represents an essential factor for the well-being of migrants in Germany (Fuchs et al, 2021;Nguyen et al, 2021). Effectively, Schwartz et al (2010) argue that it is unlikely for a person to develop a cultural identity without using their ethnic or dominant cultural context and associated practices.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed methodology for collecting and analyzing data is vital for understanding ‘hard-to-measure’ constructs and for confirming the accuracy of findings ( Bowers et al, 2013 ). Mixed methods can balance the need for generalizability and sensitivity for specific perspectives when investigating minorities’ emotional distress, even in smaller samples ( Nguyen et al, 2020 ). In this research project, the Arabic version of the questionnaire was available online in April 2020.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that refugees and other migrants may be at greater risk for stress related to the pandemic. Qiu and colleagues (2020) found that females, elderly people, people with higher education, and migrant workers among all occupations experienced the highest level of stress in a cross-sectional sample with 52,730 participants from the Chinese general population. The authors concluded that migrants might be a vulnerable population who have specific concerns and worries about viral exposure in public transportation when returning to work, and about delays in work time and consequent decrease in their income—all factors that may explain their high stress levels ( Qiu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%